Fundamental SERS Investigation of Pyridine and Its Derivates as a Function of Functional Groups, Their Substitution Position, and Their Interaction with Silver Nanoparticles - Muehlig, Anna; Cialla-May, Dana; Popp, Juergen (Journal of Physical Chemistry C, 2017)
The Raman and surface-enhanced Raman spectroscopy (SERS) spectra of pyridine, 2-, 3-, and 4-pyridinemethanol and 2-, 3-, and 4-picolylamine were comprehensively studied using two different types of silver nanoparticles as SERS substrates, namely citrate-reduced and hydroxylamine-reduced silver nanoparticles, which are the most commonly used silver colloids. For a robust band assignment, Raman spectra of the investigated molecules were simulated, applying Møller-Plesset perturbation theory in conjunction with the 6 311++G(d, p) basis set. Subsequently, the observed changes in the spectra were interpreted and discussed in detail, taking into account the simulated Raman spectra. Furthermore, differences in the spectral information resulting from the two different analyzed functional groups, the altering of the substitution position and the molecular orientation relative to the metal surface were discussed, and general conclusions for an application of those molecules as Raman reporters were derived.
CRIS-Team Scopus Importer:2023-04-20